Reviews. Issue 3 (2nd July 2020) - Moreno, Hayley; Baker, Heather; Parang, Elizabeth; Washington, Anne
Abstract: Heather Baker reviews The no-nonsense guide to leadership, management, and teamwork ; Elizabeth Parang reviews Systematic searching: Practical ideas for improving results ; Anne Washington reviews Digital preservation in libraries: Preparing for a sustainable future.